Daunorubicin and gambogic acid coloaded cysteamine-CdTe quantum dots minimizing the multidrug resistance of lymphoma in vitro and in vivo - Zhou, Yi (Int J Nanomedicine, 2016)
To minimize the side effects and the multidrug resistance (MDR) arising from daunorubicin (DNR) treatment of malignant lymphoma, a chemotherapy formulation of cysteamine-modified cadmium tellurium (Cys-CdTe) quantum dots coloaded with DNR and gambogic acid (GA) nanoparticles (DNR-GA-Cys-CdTe NPs) was developed. The physical property, drug-loading efficiency and drug release behavior of these DNR-GA-Cys-CdTe NPs were evaluated, and their cytotoxicity was explored by 3-[4,5-dimethylthiazol-2-y1]-2,5-diphenyltetrazolium bromide assay. These DNR-GA-Cys-CdTe NPs possessed a pH-responsive behavior, and displayed a dose-dependent antiproliferative activity on multidrug-resistant lymphoma Raji/DNR cells. The accumulation of DNR inside the cells, revealed by flow cytometry assay, and the down-regulated expression of P-glycoprotein inside the Raji/DNR cells measured by Western blotting assay indicated that these DNR-GA-Cys-CdTe NPs could minimize the MDR of Raji/DNR cells. This multidrug delivery system would be a promising strategy for minimizing MDR against the lymphoma.